The Relationship between Isokinetic Relative Torque of Hip, Knee and Ankle Joints and the Height of Guide Leg Jump in Young Men - Saeed Nikoukheslat; Shirin Yazdani; Ebrahim Hosseini Houri Pasand (Biyumikānīk-i varzishī)
Objective: The aim of this study was to investigate the relationship between isokinetic relative torques of hip, knee and ankle joints and the height of guide leg jump in young men.